Waste Management of High School Biology Laboratory in Yogyakarta City - Much. Fuad Saifuddin; Munna Nur Istiqomah; Na'imatul Jannah; Purwanti Purwanti; Nabilah Rahmawati; Etika Dyah Puspitasari (Universitas Tidar, 2023)
The waste processing from the high school biology laboratory is minimally handled correctly by the laboratory manager. Laboratory waste remains hazardous to the environment and dangerous to health. Schools do not have reference standards in laboratory waste management (Biology laboratory), which has the potential to cause differences in managing laboratory waste. This study aims to determine the management of high school biology laboratory waste in Yogyakarta. This qualitative descriptive study involved laboratory heads and laboratory assistants from 3 high schools; the three schools were selected by random sampling. Instruments in data collection using questionnaires, interview guide sheets, and documentation. The questionnaire consists of 19 statement items. Data were analyzed by descriptive quantitative. The results showed that in both schools, namely Schools A and B, the percentage for laboratory waste management reached 64.71% (good). In comparison, School C, the percentage for laboratory waste management reached 82.34% (very good). The average high school biology laboratory waste management in Yogyakarta City is in a good category.